2017
DOI: 10.1101/098814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myosin II activity is not required forDrosophilatracheal branching morphogenesis

Abstract: Summary statement 10Branch elongation during Drosophila tracheal development mechanistically resembles MyoII-independent 11 collective cell migration; tensile forces resulting from tip cell migration are reduced by cell elongation and 12 passive stalk cell intercalation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, other studies (Latacha et al, 2005;Nerurkar et al, 2006;Shi et al, 2014b) and our replication experiment suggested that, at least during chick heart development, myosin activity is not involved in cell rearrangement during C-looping. A recent study reporting myosin II-independent collective cell movement in the context of tracheal development in Drosophila showed that cell movement mainly depends on actin polymerization, and myosin activity is less important (Ochoa-Espinosa et al, 2017). The directional cell rearrangement observed during heart looping might be driven by similar actin-dependent mechanisms underlying such collective cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies (Latacha et al, 2005;Nerurkar et al, 2006;Shi et al, 2014b) and our replication experiment suggested that, at least during chick heart development, myosin activity is not involved in cell rearrangement during C-looping. A recent study reporting myosin II-independent collective cell movement in the context of tracheal development in Drosophila showed that cell movement mainly depends on actin polymerization, and myosin activity is less important (Ochoa-Espinosa et al, 2017). The directional cell rearrangement observed during heart looping might be driven by similar actin-dependent mechanisms underlying such collective cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Tip cell migration causes tension on the connected stalk cells due to their attachment to the dorsal trunk; as a result of this tension (or in order to release this tension), tracheal cells intercalate and subsequently extend dramatically until they are organized in a cord-like manner along the branch axis, with the most distal stalk cell remaining attached to the leading tip cell, and the most proximal stalk cell remaining attached to the dorsal trunk. Using a protein degradation method, it has recently been confirmed that actomyosin activity is indeed not required for branch formation in the tracheal system (Ochoa-Espinosa et al, 2017). It thus appears that branch formation is brought about by active tip cell migration and passive stalk cell intercalation, leading to the particular unicellular architecture of most tracheal branches (see Fig.…”
Section: Tracheal Branch Elongation Through Cell Intercalation and Cell Shape Changesmentioning
confidence: 95%
“…In tracheal branches, stalk elongation occurs in the absence of cell division and is brought about by cell intercalation and cell elongation, both triggered by the tension force exerted onto the stalk cells by the migrating tip cell (Caussinus et al, 2008). Intercalation is passive, meaning that stalk cells do not regionally deploy actomyosin forces to remodel their junctions as a driving force for intercalation (Ochoa-Espinosa et al, 2017). As a result of the intercalation process and of the small number of cells participating in it, most tracheal branches present a specific cellular architecture, being made up of cells aligned along the axis of extension in a chain-like manner, sealing the lumen via autocellular junctions and connecting to proximal and distal neighbours via ring-shaped intercellular junctions (see Fig.…”
Section: Branch Elongationmentioning
confidence: 99%
“…Self-adhesion interfaces do not form in most animal tissues, and are seen only in rare cases of tubular tissues such as blood vessels (Yu et al 2015) and in fish gill pillar cells (Kato et al 2007). The extent to which cell-autonomous myosin contractility and external pulling forces contribute to the formation and stabilization of tracheal autocellular junctions is a matter of some debate (Caussinus et al 2008;Ochoa-Espinosa et al 2017). Interestingly, the tracheal system in Tribolium larvae consists exclusively of unicellular tubules with a spiracle opening in each metamere.…”
Section: Primary Branching and Guidancementioning
confidence: 99%